The β-Adrenergic Agonist Albuterol Improves Pulmonary Vascular Reserve in Heart Failure With Preserved Ejection Fraction: A Randomized Controlled Trial. Issue 2 (18th January 2019) - Reddy, Yogesh N.V.; Obokata, Masaru; Koepp, Katlyn E.; Egbe, Alexander C.; Wiley, Brandon; Borlaug, Barry A.
Abstract : Rationale: : Pulmonary vascular resistance fails to decrease appropriately during exercise in patients with heart failure with preserved ejection fraction (HFpEF). Interventions that enhance pulmonary vasodilation might be beneficial in this cohort but could also worsen left atrial hypertension, exacerbating lung congestion. Intravenous β-agonists reduce pulmonary vascular resistance but are not suitable for chronic use. Objective: : We hypothesized that the inhaled β-adrenergic agonist albuterol would improve pulmonary vasodilation during exercise in patients with HFpEF, without increasing left heart filling pressures. Methods and Results: : We performed a randomized, double-blind, placebo-controlled trial testing the effects of inhaled albuterol on resting and exercise hemodynamics in subjects with HFpEF using high-fidelity micromanometer catheters and expired gas analysis. The primary end point was pulmonary vascular resistance during exercise. Subjects with HFpEF (n=30) underwent resting and exercise hemodynamic assessment and were then randomized 1:1 to inhaled, nebulized albuterol or placebo. Rest and exercise hemodynamic testing was then repeated. Albuterol improved the primary end point of exercise pulmonary vascular resistance as compared with placebo (−0.6±0.5 versus +0.1±0.7 WU; P =0.003). Albuterol enhanced cardiac output reserve and right ventricular pulmonary artery coupling, reduced right atrial and pulmonary artery pressures, improved pulmonary artery compliance, and enhanced left ventricular transmural distending pressure (all P <0.01), with no increase in pulmonary capillary hydrostatic pressures. Conclusions: : Albuterol improves pulmonary vascular reserve in patients with HFpEF without worsening left heart congestion. Further study is warranted to evaluate the chronic efficacy of β-agonists in HFpEF and other forms of pulmonary hypertension. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02885636. Abstract : Supplemental Digital Content is available in the text.